GESTATIONAL DIABETES MELLITUS AND SOME RELATED FACTORS IN PREGNANT WOMEN VISITING AT MILITARY HOSPITAL 103 IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and analyze factors associated with gestational diabetes mellitus (GDM) among pregnant women at 24-28 weeks of gestation attending antenatal care at Military Hospital 103 in 2025.Methods: A cross-sectional descriptive study was conducted on 195 pregnant women at 24-28 weeks of gestation attending antenatal care at Military Hospital 103 in 2025.Results: Fifty-two pregnant women were diagnosed with gestational diabetes mellitus, accounting for 26.7%. Among GDM cases, 40.4% were detected based on fasting plasma glucose levels; an additional 51.9% were diagnosed at 1 hour and 7.7% at 2 hours during the oral glucose tolerance test. The prevalence of GDM was significantly higher among women aged ≥35 years, those who were overweight, those with a first-degree family history of diabetes mellitus, a history of impaired glucose tolerance, and a previous history of gestational diabetes mellitus.Conclusion: Gestational diabetes mellitus accounted for a relatively high proportion among pregnant women at 24-28 weeks of gestation. Comprehensive screening using the oral glucose tolerance test and close monitoring of high-risk pregnant women are necessary for early detection and effective management of gestational diabetes mellitus.
Keywords: Gestational diabetes mellitus; pregnant women; Military Hospital 103…